Paris, 1866 In search of French Music - Ellis, Katharine (Oxford University Press, Oxford, 2010)
RESUMEN: La saison musicale was a collection of commissioned essays ostensibly reflecting on the 1865/66 opera and concert season in Paris. This article examines the social and critical networks represented by its contributors and explores the broader significance of both its subject matter and its silences, paying particular attention to the manner in which stereotypically post-1870 calls for renewal in French music and musical life are already pervasive by 1866-whether in relation to opera, chamber music concerts, or military band music.